Ascorbic acid-immobilized zinc selenide for electrochemical monitoring of hydrogen peroxide in liver cancer samples - Shan E Zahra Jawad; Sibtain Ahmed; Dilshad Hussain; Javerya Najeeb; Ayub Alam; Muhammad Najam-ul-Haq; Batool Fatima (Scientific Reports)
Abstract Liver cancer is globally the most frequent fatal malignancy, and its identification is critical for making clinical decisions about treatment options. Pathological diagnostics and contemporary imaging technologies provide insufficient information for tumor identification. Hydrogen peroxide (H2O2), an emerging biomarker is a powerful oxidant found in the tumor microenvironment, and stimulates the invasion, proliferation, and metastasis of liver cancer cells. This study describes a medically effective and sensitive electrochemical sensor based on ascorbic acid immobilized zinc selenide nanoparticles (AsA@Zn-Se NPs) decorated on a glassy carbon electrode (GCE) for determining H2O2 in PBS and human serum samples of liver cancer patients. The morphological and structural characterization of fabricated sensor is done by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), ultraviolet-visible (UV-Vis) spectroscopy, energy dispersive X-ray (EDX), and scanning electron microscopy (SEM). Ascorbic acid (AsA), an antioxidant for H2O2 redox behavior, is immobilized on Zn-Se NPs to aid H2O2 detection through cyclic voltammetry (CV). The sensor exhibits a low detection limit, and board linear range of 0.49 µM and 0–70 µM, respectively. The low-cost electrochemical sensor is robust for up to 100 cycles. Elecys AFP assay results validate that increasing alpha-fetoprotein (AFP) concentration, a biomarker for liver cancer, can increase the H2O2 levels in serum samples. Therefore, the proposed sensor can be used to diagnose liver cancer in clinical settings.